The challenge of making relationships central in online cultural safety education (Journal of Applied Learning and Teaching, 2024)
Cultural safety education entails the pedagogical strategy of taking students on a journey of discovery. This requires sustained openness to uncertainty, which can present myriad challenges for students and teachers. Learning about cultural safety is enabled when respectful, productive relationships characterise classrooms. In this paper, we report on the collaborative, reflective observations made by a group of university educators. We discuss educators’ efforts to facilitate positive relatedness in online classrooms compared with their experiences in shared physical space (SPS) classrooms. We found that online environments enable and constrain relational possibilities in ways that differ from SPS classrooms and which escalate educators’ emotional labour. Our findings highlight the significant role material/technological affordances of learning and teaching environments play in shaping relational possibilities. We argue that considering how the proximate materials and technologies in classrooms mediate relationship-building and connection needs to be factored into curriculum design and teaching practice. We propose drawing on culturally responsive pedagogies at the outset of cultural safety education design across SPS and online environments to prioritise relationship-building in ways that both enable students’ learning and support educators’ emotional labour.